Peran Stakeholder dalam Pencegahan Kekerasan Anak dan Pelecehan Seksual di Kabupaten Bojonegoro - Cholili, Rafika Nur; Wulandari, Septi; Kasiami, Sri (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Based on law NO. 35 0f 2024 a child is defined as someone who has not reached the agae of 18 years including unborn children. Children are also vulnerable to suffering physically, xsexually, mentally, and psycholgicallay because they are considered one of the groups that are easily victimized. According to a meta analysis the prevalence of Child Sexual Harrasement (CSA) in research from 24 countries is between 8 out of 31% of girls and 3 out of 17% of boys. This research aims to explain stakeholder involvement in mitigating violence and sexual harassment against children in Bojonegoro regency. Researchers investigate the significant issue of sexual violence and harassment targeting children and women. Researchers hope that this research will serve as a valuable resource for educational materials and as a reference for understanding and implementing sexual harassment and violence mitigation strategies. This research utilizes primary and secondary data sources. Using purposive sampling technique in selecting sources women and children Protection Empowerment Services as policy creator, Bojonegoro Regency PPA unit police and Genre Personnel as coordinators, facilitators, implementers, and accelerators. However all stakeholder are not working well in mitigating cases of violence and sexual harrasement in Bojonegoro Regency. Therefore interests are still not optimal in preventing violence and sexual harassment in Bojonegoro Regency.